A High Throughput Platform to Minimize Voltage and Fill Factor Losses - Haffner-Schirmer, Julian; Le Corre, Vincent Marc; Forberich, Karen; Egelhaaf, Hans-Joachim; Osterrieder, Tobias; Wortmann, Jonas; Liu, Chao; Weitz, Paul; Heumüller, Thomas; Bornschlegl, Andreas; Wachsmuth, Josua; Distler, Andreas; et al. (Advanced Energy Materials, 2025)
Organic photovoltaics (OPV) now can exceed 20% power conversion efficiency in single junction solar cells. To close the remaining gap to competing technologies, both fill factor and open-circuit voltage must be optimized. The Langevin reduction factor is a well-known concept that measures the degree to which charge extraction is favored over charge recombination. It is therefore ideally suited as an optimization target in high-throughput workflows; however, its evaluation so far requires expert interaction. Here, an integrated high-throughput workflow is presented, able to obtain the Langevin reduction factor within a few seconds with high accuracy without human intervention and thus suited for autonomous experiments. This is achieved by combining evidence from UV–vis spectra, current–voltage curves, and a novel implementation of microsecond transient absorption kinetics allowing, for the first time, the intrinsic determination of charge absorption cross-sections, which is crucial to reporting stationary charge densities. The method is demonstrated by varying the donor:acceptor ratio of the high performance OPV blend PM6:Y12. The high reproducibility of the method allows to find a strictly exponential relationship between the PM6 exciton energy and the Langevin reduction factor.
CRIS-Team Scopus Importer:2025-01-31
Keywords: charge dynamics; high throughput; Langevin reduction factor; organic photovoltaics; transient absorption kinetics

Molecular Oligothiophene–Fullerene Dyad Reaching Over 5% Efficiency in Single-Material Organic Solar Cells - Aubele, Anna; He, Yakun; Kraus, Teresa; Li, Ning; Mena-Osteritz, Elena; Weitz, Paul; Heumüller, Thomas; Zhang, Kaicheng; Brabec, Christoph; Bäuerle, Peter (Advanced Materials, 2021)
A novel donor–acceptor dyad, 4, in which the conjugated oligothiophene donor is covalently connected to fullerene PC71BM by a flexible alkyl ester linker, is synthesized and applied as photoactive layer in solution-processed single-material organic solar cells (SMOSCs). Excellent photovoltaic performance, including a high short-circuit current density (JSC) of 13.56 mA cm−2, is achieved, leading to a power conversion efficiency of 5.34% in an inverted cell architecture, which is substantially increased compared to other molecular single materials. Furthermore, dyad 4-based SMOSCs display excellent stability maintaining 96% of the initial performance after 750 h (one month) of continuous illumination and operation under simulated AM 1.5G irradiation. These results will strengthen the rational molecular design to further develop SMOSCs for potential industrial application.
CRIS-Team Scopus Importer:2021-09-10
Keywords: charge transport; device performance; donor–acceptor dyads; long-term stability; single-material organic solar cells

Photodegradation of Organic Solar Cells under Visible Light and the Crucial Influence of Its Spectral Composition - Weitz, Paul; Wortmann, Jonas; Liu, Chao; Wen, Tian Jiao; Li, Chang Zhi; Heumüller, Thomas; Brabec, Christoph (ACS Applied Materials and Interfaces, 2024)
While wavelength-dependent photodegradation of organic solar cells (OSCs) under visible light is typically discussed in terms of UV/blue light-activated phenomena, we recently demonstrated wavelength-dependent degradation rates up to 660 nm for PM6:Y6. In this study, we systematically investigated this phenomenon for a broad variety of devices based on different donor:acceptor combinations. We found that the spectral composition of the light used for degradation, tuned in a spectral range from 457 to 740 nm and under high irradiances of up to 30 suns, has a crucial influence on the device stability of almost all tested semiconductors. The relevance of this phenomenon was investigated in the context of simulated AM1.5 illumination with metal halide lamps and white LEDs. It is concluded that the current stability testing protocols in OSC research have to be adjusted to account for this effect to reveal the underlying physics of this still poorly understood mechanism.
CRIS-Team Scopus Importer:2024-07-26
Keywords: acceleration; high irradiances; organic solar cells; stability; wavelength dependence

Revealing Photodegradation Pathways of Organic Solar Cells by Spectrally Resolved Accelerated Lifetime Analysis - Weitz, Paul; Le Corre, Vincent Marc; Du, Xiaoyan; Forberich, Karen; Deibel, Carsten; Brabec, Christoph; Heumüller, Thomas (Advanced Energy Materials, 2022)
A method for organic solar cell (OSC) stability testing is presented that aims to provide more unique insight into the causes of degradation patterns of OSCs. The method involves using monochromatic light at high irradiation doses to accelerate isolated degradation mechanisms while monitoring the device with a series of in-situ steady-state and transient electrical measurements. The experimental results are accompanied by drift-diffusion simulations to localize degradation pathways. PM6:Y6-based OSCs are tested, which are known to show a rather broad range of lifetimes as a function of device architecture, material batches, or degradation conditions. The experiments reveal a degradation mechanism that causes an increased trap-state density inside the PM6:Y6 layer. The transient simulations suggest that these states are formed at or around the interface between the PM6:Y6 and the electron transport layer. Furthermore, the surprisingly dominant impact of the illuminating wavelength on the degradation pattern is evidenced. Lastly, the degradation rate of the devices scales linearly with light intensity, making high intensity and spectrally selective degradation the most promising way to accelerate stability testing for the faster development of stable OSCs.
CRIS-Team Scopus Importer:2022-12-09
Keywords: acceleration; drift-diffusion; organic solar cells; photodegradation; transient; wavelength-dependence

Tailoring the Nature of Interface States in Efficient and Stable Bilayer Organic Solar Cells by a Transfer-Printing Technique - Wang, Rong; Jiang, Youyu; Gruber, Wolfgang; He, Yakun; Wu, Mingjian; Weitz, Paul; Zhang, Kaicheng; Lüer, Larry; Forberich, Karen; Unruh, Tobias; Spiecker, Erdmann; Deibel, Carsten; et al. (Advanced Materials Interfaces, 2022)
Bulk heterojunction organic solar cells (BHJ-OSCs) are designed to overcome inefficient charge generation and limited exciton diffusion of organic semiconductors. However, there are some disadvantages involving inherent voltage losses, microstructure control, and operational instability. Bilayer solar cells (BL-OSCs) without mixed regions are free from these problems and offer a platform to explore the photophysical processes at the donor-acceptor interface. Here, a breakthrough for n-i-p BL-OSCs in charge generation efficiency is reported. A gradual adjustment of the molecular interface orientation of the polymer donor (PM6) is accompanied by the evolution of charge-transfer states and Forster energy transfer. Besides, less recombination losses and superior morphological stability of BL-OSCs are achieved at a PCE comparable to that of BHJ-OSCs with similar layer thickness. This investigation confirms the feasibility of manufacturing BL-OSCs by a transfer printing method and provides a versatile architecture to study fundamental interface phenomena in OSCs independent from microstructure disorder.
CRIS-Team WoS Importer:2022-04-29

Understanding Causalities in Organic Photovoltaics Device Degradation in a Machine-Learning-Driven High-Throughput Platform - Liu, Chao; Lüer, Larry; Le Corre, Vincent Marc; Forberich, Karen; Weitz, Paul; Heumüller, Thomas; Du, Xiaoyan; Wortmann, Jonas; Zhang, Jiyun; Wagner, Jerrit; Ying, Lei; Hauch, Jens; et al. (Advanced Materials, 2023)
Organic solar cells (OSCs) now approach power conversion efficiencies of 20%. However, in order to enter mass markets, problems in upscaling and operational lifetime have to be solved, both concerning the connection between processing conditions and active layer morphology. Morphological studies supporting the development of structure–process–property relations are time-consuming, complex, and expensive to undergo and for which statistics, needed to assess significance, are difficult to be collected. This work demonstrates that causal relationships between processing conditions, morphology, and stability can be obtained in a high-throughput method by combining low-cost automated experiments with data-driven analysis methods. An automatic spectral modeling feeds parametrized absorption data into a feature selection technique that is combined with Gaussian process regression to quantify deterministic relationships linking morphological features and processing conditions with device functionality. The effect of the active layer thickness and the morphological order is further modeled by drift–diffusion simulations and returns valuable insight into the underlying mechanisms for improving device stability by tuning the microstructure morphology with versatile approaches. Predicting microstructural features as a function of processing parameters is decisive know-how for the large-scale production of OSCs.
CRIS-Team Scopus Importer:2023-04-28
Keywords: device stability; Gaussian process regression (GPR) prediction; linear Pearson correlations; machine learning; organic solar cells